PENGARUH EKSTRAK BAWANG PUTIH (Alium sativum) TERHADAP GAMBARAN HISTOPATOLOGI HEPAR PADA TIKUS PUTIH (Rattus norvegicus) GALUR Sprague- dawley YANG DIINDUKSI STREPTOZOTOCIN - Fadly, Ahmad Aulia; Windarti, Indri; Hanriko, Rizki (Medula, 2024)
Diabetes Mellitus (DM) is a chronic disease characterized by blood sugar levels that exceed normal limits. Chronic DM can cause liver complications in the form of inflammation. Streptozotocin can induce mice to become a DM model and can also directly damage the liver. Garlic (Allium sativum) is a tuber that is often found in Indonesia. The various compounds contained in it have anti-diabetic and antioxidant effects which have the potential to prevent inflammation in the liver. This research was conducted to determine the effect of garlic extract (Allium sativum) on histopathological features in the form of lymphocyte cell infiltration in the portal and lobular tracts of the liver in white rats (Rattus norvegicus) of the Sprague-dawley strain induced by streptozotocin. The method used was a randomized controlled design with a pre-clinical Post-test Only Control Group Design pattern. This study used 24 mice divided into 4 groups with 6 mice in each group. The appearance of lymphocyte cell infiltration will be assessed based on the Omenetti scoring. The mean scores for lymphocyte cell infiltration in the portal tract obtained were KN=0.22, K+=2.10, P1=0.60, and P2=0.56. From the analysis using the One-Way ANOVA test followed by the Post Hoc Benferroni test, the results showed a significant difference in scores between K+ and P1 and P2. Meanwhile, the mean scores for lymphocyte cell infiltration in the lobular area obtained were KN=0.50, K+=1.16, P1=0.50, and P2=0.33. From the analysis using the Kruskal-Wallis test, no significant differences in scores were found between all groups. There was an effect of garlic extract (Allium sativum) on the infiltration of lymphocyte cells in the portal tract and no effect was found on the lobular area of ​​the liver in white rats (Rattus norvegicus) of the Sprague-dawley strain which were induced by streptozotocin.